19. Yüzyıl Tarih Yazıcılığı ve Ahmed Cevdet Paşa - Edip Uzundal (Turkish History Education Journal, 2013)
The Ottoman Historiography, on principle, is a continuation of the İslamic Historiography. Additionaly, it is formed as an “Ottoman style” because of the given work of arts on almost every kind of historiography during six hundres years. This style made a real progress through the 19th century and it absolutely came in a tone of its own. Despite the variety of the Historiography, assessing the work of arts and archived records of the worldwide historians, utilizing the other social sciences, critisizing the historian items carefully, and finally finding out the reasons and the results could came into use in the 19th century. In 19 th century, without doubt Traditional scientific historiography was Ahmed Cevdet P asha‟s business. Cevdet Pasha, not only was a statesman who was capable of law, education, and innovations on various fields but also o historian who wrote the 12 –volumeHistory of Cevdet, which is accepted as one of the most sucessful work of arts in the Ottoman Historiography, Tezâkir and Maruzât. The Works of art of Cevdet Pasha are different from the classial art in terms of his style of appoaching the events, using the western resources besides the archive resources, and the scientific method of recording.